Awakening the Sensorium in Puerto Rico’s Colonial Modernity - Cruz-Malavé, Arnaldo M. (Current Musicology, 2018)
In the summer of 1974 I visited Puerto Rico. I had migrated to the US in 1969 and completed high school here and was now returning to my island, to my homeland, as an adult, as an out gay young man with an insurrectional Afro and platform shoes seeking to connect, or better yet to reconnect, with my Puerto Rican cohorts and the thrilling, irreverent culture they were forging. It was then I rediscovered Lucecita. I remembered her from my childhood in go-go boots as I watched Alfred D. Herger’s Club del Clan on Puerto Rican TV and later at the Festival de la Canción Latina and the Ed Sullivan Show on American Spanish and English-language TV sporting a beautifully coiffed Afro, a tuxedo, and a smile. I was now at the Silvia Rexach Theater in Santurce to see her perform. The theater was packed with a diverse and motley crew, many of them gay, and next to me sat a handsome young man, apparently gay, who seemed to greet me with a smile. But everything blurred the moment that Lucecita grabbed the mic, nodded to the conductor, and thrust us into a kind of search, an infinite search, “un camino abandonado” (an abandoned path), as she sang. Every phrase turned then both familiar and unexpected, resonant with previously heard echoes yet uncanny and unhomely, and modulated in such a way that each phrase opened up to further questions, further search. I was thus suspended in this both joyful and painfully deferred becoming in which I could still hear, vividly and uncomfortably, as a buzz, an insistent running commentary coming from my handsome, presumably gay, neighbor seated next to me that filled in the gaps in Lucecita’s phrasing, displaying a minute and thorough knowledge of her biography and most recent deeds, a knowledge that claimed at every turn that she was one of us, ours, gay. Suspended between this knowing voice and Lucecita’s commanding yet open-ended sonic search I felt like I was about to burst, and when I could finally take it no more, I turned to my friendly and handsome gay comrade in arms and told him to please . . . Shut up! The reading of this beautifully crafted, exhaustively documented, and ethically inspired book by Licia Fiol-Matta, The Great Woman Singer: Gender and Voice in Puerto Rican Music, takes me back to this scene of my early youth. For The Great Woman Singer is a book about the call to open-ended aural suspension and search, about the incitement to listen to what Fiol-Matta defines as the skillfully complicated, contradictorily rich, self-reflexive, brilliant “thinking voice” that four of Puerto Rico’s greatest female pop singers, Myrta Silva, Ruth Fernández, Ernestina Reyes (La Calandria), and Lucecita Benítez, manifested in their singing during the period encompassed by the island’s process of colonial modernity and its aftermath. In tense dialogue with the social forces that would turn their powerfully odd, singular voices into mere representative “nada” or nothingness, Fiol-Matta offers in her book alternative stories of Puerto Rico’s complex and often cruel colonial modernity as told from the most intimate and ephemeral of spaces: from the grain of the singing voice that thinks as it sonically wrestles with its gendered, racialized, and class-coded conditions, the technologies of modernity in the music industries, the sonic ideologies of progress and development of the Puerto Rican Estado Libre Asociado or Commonwealth state, and forced migration and its marginalization in the urban metropolitan setting of New York. The Great Woman Singer is thus simultaneously a tentative and thoughtful reconstruction of the performances of this singing “thinking voice,” based on a painstakingly varied acopio or collection of ephemera (interviews, reviews, programs, records, cassettes, CDs, MP3s, publicity photos, album covers, posters, newspaper clippings, wardrobe, videos, films, fan recollections, and memories), and a critical pedagogy on how to listen to these voices if we are to recover not the intent of the originally sung performances but the polysemous possibilities of interpretation that these four masterfully enduring voices inscribed in them. Structured as much theoretically as poetically around the figure of nada, nothing or nothingness, The Great Woman Singer movingly tracks its overriding metaphor from Myrta Silva’s sassy and witty rendition of Rafael Hernández’s “Nada,” recorded in New York City in 1942, to Benítez’s electrifying, gut-wrenching, award-winning, apocalyptic call to begin after the atomic conflagration of the world, this time with the fire of love in Guillermo Venegas Lloveras’s song “Génesis,” at the 1969 first Festival de la Canción Latina in Mexico City. Deploying the figure of nada, Fiol-Matta seeks to register first the shocking effacement from the official archives and records of the sonic achievements of these extraordinary and influential Puerto Rican women singers and the attempted appropriations and domestications of their image and sound by the modern colonial Puerto Rican state and the music industries, as well as the no-less-distorting pressures on them by supportive left-leaning cultural nationalist intellectuals. But her book is most memorable as a performance or instantiation of the fullness of nada, of the multiple possible meanings, sonic reflections, interrogations, and affects that these artists lodged in their voice through the skillful manipulation of sound and image in an intense rhizomatic dialogue with their times, the music industries, and themselves. Conceiving voice not as we usually do, that is, as presence, fulfillment, and plenitude, but as Lacanians, such as Mladen Dolar, would have it, as petit object autre or part object that both promises fulfillment and defers it, The Great Woman Singer pursues the dialogic fullness of nothingness in the gap that opens up between the promised fulfillment and its deferral, which is where Fiol-Matta, following the example of the extraordinary women artists she studies, would like to locate us as readers and listeners. Staging a deliberate, artful negation of plenitude, she foregrounds, like these artists, the complexity, irony, ingenuity, and wit that an overriding hegemonic affect or emotion—whether this emotion is untranslatably called sentimiento, male-inflected melancholy, or sabor—would foreclose, gloss over, or suture. For the thinking of the singing voice in these artists is not the opposite of emotion or affect; it is instead what grows in the interstices and cracks of such an all-encompassing and pacifying affect when its limits are exposed and its joyful plenitude deferred. In this sense, one could say that one of the great achievements of The Great Woman Singer is to awaken in us the sensory multiplicity that underlies any attempt at imposing an all-encompassing, ideologically inflected hegemonic affect, restoring for us and for the appreciation of these great singers the dialogic dynamism of Puerto Rico’s sensorium during its period of colonial modernization that the cultural initiative of the modern colonial Puerto Rican state, tellingly named Operación Serenidad or Operation Serenity, would foreclose. To awaken the senses to the polysonic and polysemous art of reflection, to not rush to judgment and submit instead to the sonic search, to not settle for the comfortably available emotion or the easily accessible label—these are some of the many joys and deferred pleasures of reading The Great Woman Singer and Fiol-Matta’s always ethically demanding work.